THE COMMUNITY STRUCTURE OF EPILITIC DIATOM IN BUO BAY WATERS PADANG, WEST SUMATERA - Farid Febrianda; Thamrin Thamrin; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTEpilithicdiatom are one of the diatom that can withstand waves and currents, attached to hard substrates or rocks. This research was conducted from March 2018 - April 2018 located in Buo Bay Area, Padang,West Sumatra. Thegoal of this research are to determine the water quality and the structure community of epilithic diatom in Buo Bay Area, Padang, West Sumatra. The survey method was appllied in this research, sampling location were set up purposively which divided into 3 stations. Water quality measurements are carried in each station which consists of physical parameters specifically temperature, current velocity, brightness and chemical parameters consists of salinity, dissolved oxygen, acidity. Based on water quality measurement at buo baycan support the growth of epilithic diatom organism. The result showed that there were 15 genus of epilithic diatom in buo bay padang. The highest average abundance of epilithic diatoms is in station 2 was 3340.22 individual/cm2 and lowest section is in station 3 with the average of abundance value was 2741.97 individual/cm2. Key Word: Water Quality, Community Structure, Abundance, Epilitic Diatom